Gendered racial microaggressions and emerging adult Black women's social and general anxiety: Distress intolerance and stress as mediators. Issue 4 (22nd November 2022) - Burke, Lindsey A.; Chijioke, Sandra; Le, Thomas P.
Abstract: There is robust evidence that gendered racial microaggressions affect Black women's mental health. However, few studies have examined how this form of discrimination affects Black women's social anxiety in addition to their general anxiety, as well as the underlying mechanisms related to gendered racial microaggressions and anxiety. Objective: The purpose of this study was to examine the associations between gendered racial microaggressions stress (GRMS) and gendered racial microaggressions frequency (GRMF), and Black women's social anxiety and general anxiety symptoms. We also examined the mediating roles of distress intolerance and stress in these associations. Method: One hundred and sixty‐three Black women, between the ages of 18 and 25 years old, completed a cross‐sectional survey. Regression analyses were used to examine the associations between gendered racial microaggressions and social anxiety and general anxiety, and mediation analyses examined the indirect effect of gendered racial microaggressions on the outcome variables through distress intolerance and stress. Results: GRMS was associated with greater social and general anxiety through the mechanisms of distress intolerance and stress. GRMF was associated with reduced social anxiety and was not associated with general anxiety. Conclusions: Intervention efforts should be aimed to prevent the experience of gendered racial microaggressions to prevent subsequent stress and mental health outcomes for Black women.